ASEAN-U.S Cooperation on Renewable Energy: ASEAN’s Response to Climate Change Phenomenon - Dewi Agha Putri (Intermestic: Journal of International Studies, 2018)
Climate change phenomenon has become one of the major issues discussed in the Association of Southeast Asian Nations (ASEAN). ASEAN as one of the most influential regions in the world tries to combat climate change by developing renewable energy and creating a better living in the region. To pursue its ambition, ASEAN cooperates with United States of America (U.S) as one of its dialogue partners following the implementation of the ASEAN Plan of Action for Energy Cooperation (APAEC) 2016-2025. This paper is using qualitative research method through secondary data analysis to explain how ASEAN-U.S cooperation on renewable energy helps ASEAN to combat climate change. Throughout the research, ASEAN-U.S cooperation on renewable energy is potentially beneficial and helpful for ASEAN to pursue its ambition in terms of investment provision and technology and information exchange.